The value of design in retail and branding - Quartier, Katelijn (Emerald Publishing Limited, 2021)
Scholarly studies of value creation for consumer experience constitute a very fragmented field, spanning the disciplines of design, branding and marketing. The Value of Design in Retail and Branding creates a much-needed bridge between different disciplines involved in retail design, bringing together a range of research and insights for practice in these disciplines, improving the impact of design. Here Katelijn Quartier, Ann Petermans, TC Melewar and Charles Dennis bring together a team of field-leading, practice-based experts in order to offer an interdisciplinary, practice-oriented inquiry into how design plays a key role in defining a successful retail environment and experience. In four sections organised around the concepts of design, experience, context, and interdisciplinarity, contributors highlight how to achieve impactful branding and retail-experience design through a focus on such issues as local relevance and storytelling. As each chapter concludes by explaining how its findings can feed into practice, this book begins filling the gap between academic journals and visual case studies, ultimately providing fertile ground for further debate around best practice. For its interdisciplinary approach, its scholarly rigour, and its clearly articulated implications for practice, The Value of Design in Retail and Branding is of interest to scholars of design, branding and marketing as well as to practitioners within these fields.